KOLERASIANTARADISIPLINBELAJARDAN HASILBELAJARSISWAKELASVPADAPEMBELAJARANTEMATIK - Neneng Sapitri; Kartono Kartono; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe research aims to describe whether there is a correlation between learning discipline and learning outcomes for fifth grade students in thematic learning at SDN 34 Pontianak City. The research method is a descriptive method in the form of a correlation study. The research population is all fifth grade students at SDN Pontianak Kota. Sampling used a sampling technique with a sample size of 30 students of class V SDN Pontianak Kota. Data collection techniques, namely, indirect communication techniques and documentary studies. Indirect communication techniques are used to collect data on learning disciplines with a tool in the form of questionnaires, while documentary techniques are used to collect data on learning outcomes for class V SDN Pontianak Kota. The data analysis technique was carried out by statistical analysis showing student learning disciplines on average 85, student learning outcomes on average 87 and the correlation between learning disciplines and student learning outcomes of r _(count) greater than r_(Table) at a significant level 5% with the number 0.660 > 0.361. There is a positive and significant correlation between learning discipline and the learning outcomes of fifth graders at SD N 34 Pontianak City, with a strong correlation.Keywords: Correlation, Learning Discipline, Learning Outcomes, and Thematic Learning